2016
DOI: 10.1038/srep20940
|View full text |Cite
|
Sign up to set email alerts
|

The TRPM1 channel in ON-bipolar cells is gated by both the α and the βγ subunits of the G-protein Go

Abstract: Transmission from photoreceptors to ON bipolar cells in mammalian retina is mediated by a sign-inverting cascade. Upon binding glutamate, the metabotropic glutamate receptor mGluR6 activates the heterotrimeric G-protein Gαoβ3γ13, and this leads to closure of the TRPM1 channel (melastatin). TRPM1 is thought to be constitutively open, but the mechanism that leads to its closure is unclear. We investigated this question in mouse rod bipolar cells by dialyzing reagents that modify the activity of either Gαo or Gβγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 61 publications
1
29
0
1
Order By: Relevance
“…In attempt to reconcile these findings a more recent study employed a panel of manipulations, which sequester and activate both Gβγ and Gα o under both dark- and light-adaptated conditions. This study reported evidence that both Gα and Gβγ are involved in regulation of native ON-BC transduction channels (Xu et al 2016). Furthermore, evidence in transfected cells suggest that both Gα and Gβγ are capable of interacting directly with the TRPM1 protein (Xu et al 2016).…”
Section: Heterotrimeric G Proteins Transfer Light-evoked Signals Frommentioning
confidence: 95%
See 3 more Smart Citations
“…In attempt to reconcile these findings a more recent study employed a panel of manipulations, which sequester and activate both Gβγ and Gα o under both dark- and light-adaptated conditions. This study reported evidence that both Gα and Gβγ are involved in regulation of native ON-BC transduction channels (Xu et al 2016). Furthermore, evidence in transfected cells suggest that both Gα and Gβγ are capable of interacting directly with the TRPM1 protein (Xu et al 2016).…”
Section: Heterotrimeric G Proteins Transfer Light-evoked Signals Frommentioning
confidence: 95%
“…This study reported evidence that both Gα and Gβγ are involved in regulation of native ON-BC transduction channels (Xu et al 2016). Furthermore, evidence in transfected cells suggest that both Gα and Gβγ are capable of interacting directly with the TRPM1 protein (Xu et al 2016). The proposed model (Figure 2) indicates that the interaction of TRPM1 with both free Gβγ and Gα o -GTP is required to close fully transduction channels, and that re-arrangement between the subunits upon their inactivation removes the inhibitory constraint allowing channels to open (Xu et al 2016).…”
Section: Heterotrimeric G Proteins Transfer Light-evoked Signals Frommentioning
confidence: 95%
See 2 more Smart Citations
“…Conversely, they are inhibited by (1) certain clinically approved drugs including nonsteroidal anti-inflammatory drugs (NSAIDs, e.g., mefenamic acid), antibiotics (e.g., voriconazole, which also inhibits TRPM1 channels), sex-steroids (e.g., progesterone), and synthetic drug-like antagonists [40,41,51,61,[67][68][69][70][71][72]; (2) naturally occurring plant-derived secondary metabolites (e.g., citrus flavanones) [73][74][75]; and (3) Gprotein coupled receptor βγ subunits [76][77][78][79]. By contrast, TRPM1 channels were found to be inhibited by interaction with both Gα or Gβγ subunits [80].…”
Section: Introductionmentioning
confidence: 99%